can someone help me simplify 2a^2b^3(4a^2+3ab^2-ab)=? the first part of the answer is 8a^4

4 answers

not quite, you forgot the b part

1st term ---- 8a^4 b^3
etc.
2a^2b^3(4a^2+3ab^2-ab)
= 2a^2b^3*4a^2
+ 2a^2b^3*3ab^2
- 2a^2b^3*ab

= 8a^4b^3 + 6a^3b^5 - 2a^3b^4
i don't know whats after that i got +6a^3b^5-2a^3b^4. is it right?
ty
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
    1. answers icon 1 answer
  2. When answering a 2 part question, it's important to...Answer the questions independently Use the test to take the test: look at
    1. answers icon 1 answer
  3. Simplify the expression.(-4)^-6(-4)^-7 My answer: -4 Simplify and give the answer in scientific notation. (5 X 10^6((3 X 10^5)
    1. answers icon 6 answers
more similar questions